Genome-wide association study identifies multiple susceptibility loci for multiple myeloma - Jonathan S. Mitchell (Nature Portfolio, 2016)
Previous genome-wide association studies have identified loci associated with the risk of multiple myeloma. Here, the authors present a meta-analysis of six genome wide association studies of the disease and identify eight new loci; functional studies identify genes as candidates for the basis of these associations.